Twisted Grosse–Wulkenhaar φ4 model: dynamical noncommutativity and Noether currents - HOUNKONNOU, MAHOUTON NORBERT; OUSMANE SAMARY, DINE (My University, 2010)
This paper addresses the computation of Noether currrents for the renormalizable Grosse–Wulkenhaar φ4 model subjected to a dynamical noncomutativity realized through a twisted Moyal product. The noncommutative energy–momentum tensor, angular momentum tensor and the dilatation current are explicitly derived. The breaking of translation and rotation invariances has been avoided via a constraint equation.
Keywords: Twisted field theory